Ionic liquid assisted hydrothermal synthesis of MoS2 double-shell polyhedral cages with enhanced catalytic hydrogenation activities. Issue 38 (28th April 2017) - Li, Jiahe; Wang, Donge; Ma, Huaijun; Li, Min; Pan, Zhendong; Jiang, Yuxia; Tian, Zhijian
Abstract : MoS2 double-shell polyhedral cages are synthesized via an ionic liquid assisted hydrothermal route and exhibit enhanced catalytic hydrogenation properties. Abstract : MoS2 double-shell polyhedral cages are synthesized via an ionic liquid assisted hydrothermal process, in which the polyhedral cages of organic–inorganic hybrid phosphomolybdic acid-ionic liquids (PMA-ILs) are formed in situ and serve as a sacrificial template. The as-synthesized MoS2 hierarchical polyhedral cages have a lateral length of 0.5–1.5 μm and average shell thickness of about 150 nm. The surfaces of MoS2 double-shell polyhedral cages are very rough and composed of small nanosheets. The synthesis parameters including ionic liquid dosage, crystallization time and sulfur source are investigated to clarify the growth mechanism. Polycyclic aromatic hydrocarbons including naphthalene and anthracene were used as model compounds to evaluate the catalytic hydrogenation performance of the as-synthesized MoS2 sample. It turns out that MoS2 double-shell polyhedral cages manifest better catalytic hydrogenation activities than MoS2 nanoparticles and commercial bulk MoS2 . The double-shell hollow structure and the vertical-alignment of nanosheets in the polyhedral shell are responsible for the enhanced catalytic activities of MoS2 double-shell polyhedral cages.